2023
DOI: 10.1523/eneuro.0480-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Neuroadaptations in the Nucleus Accumbens Core Accompany Incubation of Methamphetamine Craving in Male and Female Rats

Abstract: Relapse is a major problem in treating methamphetamine use disorder. ‘Incubation of craving’ during abstinence is a rat model for persistence of vulnerability to craving and relapse. While methamphetamine incubation has previously been demonstrated in male and female rats, it has not been demonstrated after withdrawal periods greater than 51 days and most mechanistic work used males. Here we address both gaps. First, although methamphetamine intake was higher in males during self-administration training (6 h/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Regarding incubation of methamphetamine craving, previous studies reported no sex differences in incubation of methamphetamine craving after either forced abstinence [ 10 , 12 , 14 , 26 ] or voluntary abstinence [ 31 , 32 ], similar to incubation studies using heroin [ 31 ] and oxycodone [ 33 ]. These findings are in contrast with previous preclinical studies demonstrating higher cue-induced cocaine seeking in female rats than male rats after forced abstinence [ 34 36 ].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Regarding incubation of methamphetamine craving, previous studies reported no sex differences in incubation of methamphetamine craving after either forced abstinence [ 10 , 12 , 14 , 26 ] or voluntary abstinence [ 31 , 32 ], similar to incubation studies using heroin [ 31 ] and oxycodone [ 33 ]. These findings are in contrast with previous preclinical studies demonstrating higher cue-induced cocaine seeking in female rats than male rats after forced abstinence [ 34 36 ].…”
Section: Introductionmentioning
confidence: 54%
“…For example, we demonstrated a critical role of dorsal striatum in this incubation in male rats [ 9 ]. A growing number of studies also began to examine neuroadaptations associated with incubation of methamphetamine craving in female rats [ 10 17 ], but only one published study has taken estrous cycle into consideration [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The females in our initial dose-response study consumed more MA from each of the three concentrations tested during the 7-day course of self-administration, relative to the males (Figure 2B). While we have reported higher oral MA intakes during the acquisition of oral MA self-administration in females versus males [17], inconsistencies exist in the literature pertaining to sex differences in MA consumption under intravenous MA self-administration by rats [49][50][51][52][53], in low-concentration (0.02-0.08 g/L) MA drinking in the home cage by mice (e.g., [19][20][21]), and in MA intake under oral operant-conditioning procedures in both mice [17,18] and rats [24,25]. Indeed, we failed to detect any sex differences in the dose-response function for MA intake across an approximately 100-fold range of MA concentrations (0.025-3.2 g/kg) in our recent oral operant-conditioning study, despite females consuming 0.1 g/L MA more than males during the acquisition phase of the experiment [17], and we detected no sex differences in the intake of the 3.2 g/L MA solution in either of our two follow-up behavioral pharmacological studies.…”
Section: B6j Mice Consume Very Large Amounts Of Ma Under Limited-acce...mentioning
confidence: 62%
“…Given the variations in the mechanisms of action among different stimulants, the effectiveness of AMPA/kainate antagonist treatment may differ depending on the specific drug. For example, when comparing the behavioral effects and subsequent neuroadaptations related to incubation of craving for cocaine and methamphetamine, numerous distinctions in glutamate synaptic plasticity in the nucleus accumbens core were reported (Scheyer et al, 2016;Murray et al, 2019;Funke et al, 2023). Hence, it is important to note that cocaine and amphetamine should not be grouped together when discussing the role of glutamate-related plasticity.…”
Section: Discussionmentioning
confidence: 99%